Analisis Pembagian Nisbah Bagi Hasil terhadap Pembiayaan Syariah Akad Mudharabah - Cut Mutia; Rayyan Firdaus (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Mudharabah contracts are the main type of choice that people are interested in for sharia financing. Mudarabah is an agreement in which an item is sold at cost price plus profit, with the seller obliged to transparently disclose the purchase amount to the buyer, including the profit margin received. This research uses the Literature Review method, namely comparing and analyzing theories that are relevant to the research problem being faced. The aim of the research is to analyze further how the profit sharing ratio is distributed in mudharabah contracts, as well as analyze what sharia principles are applied during the mudharabah agreement process so that there are no misperceptions when the contract is agreed to take place. Of the research can provide information regarding the mechanism for distributing the ratio for the proceeds of mudharabah contracts and are expected to be able to apply sharia principles at the time of the contract.